A comprehensive clinical review of opioid-induced allodynia: Discussion of the current evidence and clinical implications - Hayes, PharmD, MPH, Corey J.; Painter, PharmD, MBA, PhD, Jacob T. (Journal of Opioid Management, 2017)
Opioid analgesics are one of the most often prescribed medication classes, and their use has increased dramatically, with the number of prescriptions doubling between 1998 and 2010. Moreover, long-term use of opioids is becoming more prevalent. The complications arising from opioid use have been clearly documented; however, a relatively unknown complication potentially linked to opioid use is allodynia. This article outlines how research on opioid-induced hyperalgesia has led to the discovery of allodynia. Next, this article provides a detailed review of the current literature on allodynia, which includes animal studies, case reports, case series, and randomized controlled trials. Finally, the authors provide some potential clinical implications and applications for clinicians in regards to prescribing practices of opioids in the presence of allodynia.